Escalation Students’ Academic Achievement Through Soft Skills Training and Academic Resilience - Efi Miftah Faridli; Fatmah Bagis; Sabar Narimo; Endang Fauzi; Anam Sutopo (EDUCATION JOURNAL OF INDONESIA, 2024)
Improvement of academic achievement is the main factor in improving the quality of education in University of Purwokerto City . This study aims to empirically examine how soft skills training and academic resilience affect student academic achievement in higher education with social recognition theory.  The use of the method uses a quantitative descriptive approach. The distribution of the questionnaire was carried out openly during the training of 461 students who were studying in the 2nd semester at university. Analysis using Smart-PLS (Partial Least Squares). As a result, soft skill training had a significant influence on student academic achievement (accepted) with p-values (0.000 > 0.05). Resilience had a negligible influence on students' academic achievement based on p-values (0.708 < 0.05). This research contributes to universities to provide support for improving student achievement by supporting student skills and universities need to pay attention to the level of resilience so that students are ready to face difficulties in the future. Keyword : Soft Skills Training, Resilience, Academic Achievement.